Géographie de la dispersion des migrations subsahariennes au Maroc - Sofia El Arabi (Les Cahiers d’EMAM)
At the very heart of this research work lies the dispersal policy translated into forced displacement of sub-Saharan migrants from the north of Morocco to medium-sized cities located further south. Based on an empirical study in the framework of an action research, our surveys were conducted comparatively in the medium-sized cities of Tiznit and Taza. Our research aims at highlighting the effects of dispersal, related to the process of “bordering” and the emergence of refuge cities where palliative reactions feed the reconfiguration of reception and urban inclusion missions.